The "Santānagopāla" as a Narrative Opening up Intimate Spaces: Lakṣmī Tampurāṭṭi and Her Poem - Lidia Sudyka (Ksiegarnia Akademicka Publishing, 2018)
The "Santānagopāla" as a Narrative Opening up Intimate Spaces: Lakṣmī Tampurāṭṭi and Her Poem